Multilateral collaborative partnerships and digital innovation in agri-food systems - Metcalfe, Hannah; Gardeazabal Monsalve, Andrea (International Food Policy Research Institute, 2024)
The digital transformation of food, land, and water (FLW) systems holds potential for sustainability and resilience but remains hindered by fragmentation, infrastructure deficits, and governance gaps. Unlike fintech and healthcare, where structured digital adoption has flourished, FLW systems require multilateral collaborative partnerships to scale innovations effectively. This working paper examines five case studies from Latin America, Africa, and South Asia, highlighting how strategic partnerships—including those led by CGIAR, IICA, AGRA, and private sector actors— drive digital adoption. Findings reveal that successful collaboration hinges on two interdependent processes: a technical process for identifying digital solutions and an incentive process for aligning stakeholder interests. Trust-building, clear governance, and equitable participation emerge as key enablers. Lessons from fintech and healthcare emphasize the need for regulatory clarity, interoperable data frameworks, and inclusive financing models to scale digital transformation. Moving forward, addressing data sovereignty, power asymmetries, and financing constraints through structured partnerships will be essential for unlocking the full potential of digital innovation in FLW systems.